Empathy : an interdisciplinary journal for persons working to end oppression on the basis of sexual identities. (Columbia : Gay and Lesbian Advocacy Research Project, 1992)
Fonds Suzan Daniel (FSD)
Periodiciteit: halfjaarlijks
Redactie: PO Box 5085, Columbia SC 29250
Engels
Periodiek